2011
DOI: 10.3138/jsp.42.2.243
|View full text |Cite
|
Sign up to set email alerts
|

The Peer-Review Process for Articles in Iran's Scientific Journals

Abstract: The purpose of this research was to study the peer-review process for articles in Iran's accredited scientific journals. The study considered the types of refereeing currently practised, the decision-making methods and criteria for acceptance of articles, the major decision makers, and the current norms in the peer-review process. The method used was a survey, and the data-collecting tool was a questionnaire. The statistical population of this research included 245 scientific journals. The results of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The rise in computational power allows us to investigate the ever-increasing complexity of the human phenomenon. However, the competence of those who evaluate, review or make decisions on papers also plays a major role in the publishing process (Ardakan, Mirzaie, & Sheikhshoaei, 2011;Bussin, 2019). It is clear that reviewers and/or section editors in SAJIP also might not always have the required competence to understand the latest analytical methods and, therefore, skip over such methods 3 .…”
Section: Responsementioning
confidence: 99%
“…The rise in computational power allows us to investigate the ever-increasing complexity of the human phenomenon. However, the competence of those who evaluate, review or make decisions on papers also plays a major role in the publishing process (Ardakan, Mirzaie, & Sheikhshoaei, 2011;Bussin, 2019). It is clear that reviewers and/or section editors in SAJIP also might not always have the required competence to understand the latest analytical methods and, therefore, skip over such methods 3 .…”
Section: Responsementioning
confidence: 99%
“…The language in which the science is written and the size of the scientific community are additional sources of diversity. Furthermore, numerous limitations of peer review and resultant scientific corruption have been reported by editors of small journals around the world (1-3). …”
mentioning
confidence: 99%
“…Poor research environment and infrastructure, lack of adherence to high-standard editorial policies, restricted access to information sources, and communication difficulties with the reviewers impede the peer review in these countries (28,29). To use an extreme example, a recent survey of 245 Iranian scientific journals suggested that their editors struggle with external peer review and make decisions largely based on in-house comments (30). …”
mentioning
confidence: 99%